Pashto Contemporary Writer: Nasir Ahamd Ahmadi’s Contribution in Novel and Short Story Writing - Adabpal, Zabihullah; Bazgar, Omaid; Sidiqui, Hafeezulhaq; Mahmoodi, Zubair Ahmad; Mohammadi, Kabir Ahamd; Rahman, Sayed (Talenta Publisher, 2025)
There is abundant Pashto contemporary literature throughout the country produced by staunchest Afghan writers who depicted the literary, social, cultural, political, and religious aspects of the society. Yet, there is little information, particularly in English language, about the literary life and contribution of Nasir Ahamd Ahmadi. The study aims to disseminate the biographical and literary information about Ahmadi in English. It also provides his literary contribution in modern Pashto literature. The analysis revealed that Lat. Ahmadi was famous for his Pashto novels because of his sweet, local color, and simple linguistic terms. He was a fluent and eloquent writer of Pashto modern novels and short stories which are written for the purpose of reforming Afghan society morally. And, he has published more than twenty five works among which Jojo (2013), Baghdadi Pir (2016), and Akh Watana! (2018) novels had been a lot of popular. The data were primarily collected through Arts students’ monographs in Pashto Departments including some personal communications. Some books were also reviewed in the central library of at Kandahar University for data collection which was analyzed thematically and translated into English professionally. The findings suggest that many Pashtun critics and students love Ahmadi’s artistic works especially the novels and short stories. It seems quite essential that not only his literary life and achievements have to be researched in native languages but it is significant that one of his best novels needs to be translated into English language for a large number of international audiences. Keywords: Pashto Novels and Short Stories, Nasir Ahmad Ahmadi, Literary Contribution